Optimization Design of Dynamic Thermal Boundary Carburizing Quenching Process for Spiral Bevel Gear - Liu Fuyang; Liu Ganhua; Xie Xianfeng; Zou Yang (Jixie chuandong)
In order to solve the problem that the drum length is too large and the hardness of the tooth surface is less than the requirement of noise,vibration and acceleration of the gear pair,the DEFORM-HT finite element software is used to simulate the spiral bevel gear. The effects of the four main parameters such as the temperature of the cooling medium,the inlet speed of the quenching tank,the temperature of the gear insulation and the carbon potential of the cooling and diffusion stage on the drum length and tooth surface hardness are studied. Secondly,the orthogonal experimental design and analysis method is used to optimize the index of gear drum length and tooth surface hardness. The optimum process parameters are obtained by numerical analysis of variance and variance. Finally,the results show that when the medium temperature is 100 ℃,the inlet speed is1. 5 m/s,the holding temperature is 835 ℃,the carbon potential is 1. 0%,the drum length is the smallest,the hardness of tooth surface satisfies the hardness requirement of the actual production.